In vivo Cigarette Smoke Exposure Decreases CCL20, SLPI, and BD-1 Secretion by Human Primary Nasal Epithelial Cells - Jukosky, James; Gosselin, Benoit J.; Foley, Leah; Dechen, Tenzin; Fiering, Steven; Crane-Godreau, Mardi A. (Frontiers in Psychiatry, 2016)
Abstract Smokers and individuals exposed to second hand cigarette smoke (SHCS) have a higher risk of developing chronic sinus and bronchial infections. This suggests that cigarette smoke (CS) has adverse effects on immune defenses against pathogens. Epithelial cells are important in airway innate immunity and are the first line of defense against infection. Airway epithelial cells form a physical barrier, but also respond to the presence of microbes by secreting antimicrobials, cytokines and chemokines. These molecules can lyse infectious microorganisms and/or provide signals critical to the initiation of adaptive immune responses. We examined the effects of cigarette smoke on antimicrobial secretions of primary human nasal epithelial cells (PHNEC). Compared to non-CS exposed individuals, PHNEC from in-vivo cigarette smoke exposed individuals secreted less CCL20, BD-1, and SLPI apically, less BD-1 and SLPI basolaterally, and more CCL20 basolaterally. Cigarette smoke extract (CSE) exposure in vitro decreased the apical secretion of CCL20 and beta defensin-1 by PHNEC from non-CS exposed individuals. Exposing PHNEC from non-CS exposed to cigarette smoke extract also significantly decreased the levels of many mRNA transcripts that are involved in immune signaling. Our results show that in-vivo or in vitro exposure to cigarette smoke alters the secretion of key antimicrobial peptides from PHNEC, but that in-vivo CS exposure is a much more important modifier of antimicrobial peptide secretion. Based on the gene expression data, it appears that cigarette smoke extract disrupts multiple immune signaling pathways in PHNEC. Our results provide mechanistic insight into how cigarette smoke exposure alters the innate immune response and increases an individual’s susceptibility to pathogen infection.